2017
DOI: 10.1007/s00705-017-3525-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of infectious pancreatic necrosis viruses isolated from farmed fish in Finland

Abstract: Infectious pancreatic necrosis virus (IPNV) has been isolated annually since 1987 from salmonids without clinical signs at coastal fish farms in Finland. In the inland area, viral isolations were rare until 2012, when IPNV was detected at several freshwater fish farms. Between 2013 and 2015, the infection spread and IPNV was continuously isolated from several farms, both inland and on the coast. The aim of this study was to genetically characterise the IPNV isolates collected from Finnish coastal and inland fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…On the other hand, stress is an important parameter influencing the disease, and in the farming system it depends on the physicochemical conditions of the water, inappropriate nutrition, manipulation of the fish, and the density of the fish population in the facility. To this regard, the excessive density of cultured fish, a very important and often ignored parameter, has a double effect on the artificial environment in farms: on the one hand, it provokes stress in the fish, which is known to affect host defenses and has been reported to trigger outbreaks in asymptomatic carriers [78,79]; on the other hand, high fish densities favor virus transmission and virus evolution to high virulent types [80]. Therefore, it is clear that fish density represents a very important parameter in fish mortalities by IPNV.…”
Section: The Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, stress is an important parameter influencing the disease, and in the farming system it depends on the physicochemical conditions of the water, inappropriate nutrition, manipulation of the fish, and the density of the fish population in the facility. To this regard, the excessive density of cultured fish, a very important and often ignored parameter, has a double effect on the artificial environment in farms: on the one hand, it provokes stress in the fish, which is known to affect host defenses and has been reported to trigger outbreaks in asymptomatic carriers [78,79]; on the other hand, high fish densities favor virus transmission and virus evolution to high virulent types [80]. Therefore, it is clear that fish density represents a very important parameter in fish mortalities by IPNV.…”
Section: The Environmentmentioning
confidence: 99%
“…The capacity of the host to defend against virus invasion and proliferation, its immune response-described in Section 3.3-depends, to a large extent, on its physiological state, and stress has a great influence on it and hence on the reduction of the effectivity of the defense barriers and on the development of the disease [78,79,81]. Another approach to understand the variable susceptibility of fish is more related to genetics, since it has been demonstrated that different lines of the same species, with the same age, and under the same conditions, can respond differently to infection of the same viral strain.…”
Section: The Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a sprivivirus was isolated from all fish species in this infection trial (Table 2). Spriviviruses grow in the same cell cultures as those used for VHSV isolation and were confirmed by sequencing (Holopainen et al 2017).…”
Section: Infection Trial In Field Conditionsmentioning
confidence: 94%
“…The probe was 5'-end labelled with FAM and 3'-end labelled with TAMRA (Table 3). We used a threshold cycle (C t ) cut-off value of 36 as estimated in our earlier study (Vennerström et al 2017).…”
Section: Real-time Rt-pcr For Examining the Presence Of Vhsv From Tismentioning
confidence: 99%